Pedagogias populares e epistemologias feministas latino-americanas - Silva, Márcia Alves da (2019)
Several Latin American studies problematize traditional European and androcentric positivist science but are still scarcely visible in the universities of the global South. This book brings together the experiences of some Latin American researchers who develop studies and research in a decolonial, post-secondary, and/or feminist perspective.